2010
DOI: 10.1677/joe-10-0081
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of feeding suppression by the anorexigenic hormones neuromedin U and neuromedin S in rats

Abstract: We compared the central mechanisms of feeding suppression by the anorexigenic hormones neuromedin U (NMU) and neuromedin S (NMS) in rats. I.c.v. injection of either NMU or NMS dose dependently decreased 3-h food intake during the first quarter of a dark period. Pretreatment involving i.c.v. injection of a specific anti-NMS IgG blocked the suppression of food intake induced by i.c.v.-and i.p.-injected leptin, but anti-NMU IgG elicited no blockade. Quantitative PCR analysis revealed that i.c.v. injection of NMU … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 44 publications
1
12
0
Order By: Relevance
“…administration of NmU to rats induced stress-related behavior (37,(63)(64)(65)(66). This was coupled to an increase in c-Fos expression, increased depolarization, and neuronal firing by cells of the PVN following NmU administration (67)(68)(69)(70)(71). Moreover, significant increases in plasma concentrations of stressrelated hormones (ACTH, corticosterone, adrenalin) were also detected following central or subcutaneous administration of NmU; these results are in agreement with low ACTH plasma concentrations detected in NmU Ϫ/Ϫ mice (57,65,69,(72)(73)(74)(75).…”
Section: Stress Responsesupporting
confidence: 81%
“…administration of NmU to rats induced stress-related behavior (37,(63)(64)(65)(66). This was coupled to an increase in c-Fos expression, increased depolarization, and neuronal firing by cells of the PVN following NmU administration (67)(68)(69)(70)(71). Moreover, significant increases in plasma concentrations of stressrelated hormones (ACTH, corticosterone, adrenalin) were also detected following central or subcutaneous administration of NmU; these results are in agreement with low ACTH plasma concentrations detected in NmU Ϫ/Ϫ mice (57,65,69,(72)(73)(74)(75).…”
Section: Stress Responsesupporting
confidence: 81%
“…Administration of NMU could not suppress food intake or increase oxygen consumption and body temperature in CRH-knockout mice (Hanada et al 2003). Administration of NMS could upregulate the CRH mRNA levels in the brain, and the NMS-mediated inhibition of food intake could be attenuated by pretreatment with the antagonist of CRH , Nakahara et al 2010. In goldfish, a significant increase in the expression of crh mRNA was observed after injection with Nmu-21 peptide, and the anorexigenic effect of this peptide was erased by treatment with the antagonist of Crh receptor (Maruyama et al 2008).…”
Section: Discussionmentioning
confidence: 94%
“…The effects of NMU signaling on total food consumption have been previously examined (514,18, 21, 35, 36). It has been shown that intra-PVN and ICV NMU regulate intake of a standard diet in rodents and that NMUR2 mediates preference for high-fat food (9).…”
Section: Resultsmentioning
confidence: 99%
“…However, further understanding of the regions and pathways involved is essential to interpreting the behavioral effects of NMU. While the effects of NMU on food intake and body weight have been evaluated (8, 11, 1821), little consideration has been given to the reinforcing properties of food. However, NMU has recently been shown to regulate the reinforcement value of alcohol (22), and signaling between NMU and its CNS receptor, NMUR2, regulates preference for obesogenic food (9).…”
Section: Introductionmentioning
confidence: 99%